How snoRNAs can contribute to cancer at multiple levels - Federico Zacchini; Chiara Barozzi; Giulia Venturi; Lorenzo Montanaro (2024)
Abstract snoRNAs are a class of non-coding RNAs known to guide site specifically RNA modifications such as 2′-O-methylation and pseudouridylation. Recent results regarding snoRNA alterations in cancer has been made available and suggest their potential evaluation as diagnostic and prognostic biomarkers. A large part of these data, however, was not consistently confirmed and failed to provide mechanistic insights on the contribution of altered snoRNA expression to the neoplastic process. Here, we aim to critically review the available literature on snoRNA in cancer focusing on the studies elucidating the functional consequences of their deregulation. Beyond the canonical guide function in RNA processing and modification we also considered additional roles in which snoRNA, in various forms and through different modalities, are involved and that have been recently reported.